2016
DOI: 10.1136/gutjnl-2015-311314
|View full text |Cite
|
Sign up to set email alerts
|

Integrative microRNA profiling in alcoholic hepatitis reveals a role for microRNA-182 in liver injury and inflammation

Abstract: AH is characterised by a deregulated miRNA profile, including miR-182, which is associated with disease severity and liver injury. These results highlight the potential of miRNAs as therapeutic targets and biomarkers in AH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
83
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 50 publications
1
83
0
2
Order By: Relevance
“…In a study that reported a histological scoring system to determine severity of AH, presence of cholestasis was found to be an independent predictor of increased mortality . In another study, the microRNA profile of AH patients was analyzed and found to reflect changes observed in cholestatic liver diseases . These findings collectively suggest that cholestasis is a frequent complication of AH and may even portend a worse outcome.…”
Section: Discussionmentioning
confidence: 97%
“…In a study that reported a histological scoring system to determine severity of AH, presence of cholestasis was found to be an independent predictor of increased mortality . In another study, the microRNA profile of AH patients was analyzed and found to reflect changes observed in cholestatic liver diseases . These findings collectively suggest that cholestasis is a frequent complication of AH and may even portend a worse outcome.…”
Section: Discussionmentioning
confidence: 97%
“…21, 33 It has been reported that overexpression of miR-182 induces the production of inflammatory mediators in biliary cells and increase liver damage, bile acid accumulation, and inflammatory responses in mice. 34 However, the role of miR-182 in atherogenesis remained unclear. In the present study, we found that miR-182 promoted LPL expression, lipid accumulation, and proinflammatory cytokine secretion by targeting HDAC9 in THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Blaya D et al also identified 177 differentially expressed miRNAs in the liver of ALD patients (Blaya et al, 2016). In their studies, RNA samples from liver tissue of patients with severe AH, alcoholic cirrhosis, cirrhosis from hepatitis C, and healthy patients were examined and compared.…”
Section: The Role Of Microrna In Inflammation Of Aldmentioning
confidence: 99%
“…MiR-182 mimic induced an upregulation of inflammatory mediators in biliary cells, suggest that miR-182 promotes liver inflammation by targeting biliary epithelial cells (Blaya et al, 2016). …”
Section: The Role Of Microrna In Inflammation Of Aldmentioning
confidence: 99%